2017
DOI: 10.2147/dddt.s139248
|View full text |Cite
|
Sign up to set email alerts
|

Current perspective on rituximab in rheumatic diseases

Abstract: The steadily increasing knowledge regarding pathogenetic mechanisms in autoimmune rheumatic diseases has paved the way to different therapeutic approaches. In particular, the market entry of biologics has dramatically modified the natural history of rheumatic chronic inflammatory diseases with a meaningful impact on patients’ quality of life. Among the wide spectrum of available biological treatments, rituximab (RTX), first used in the treatment of non-Hodgkin’s lymphoma, was later approved for rheumatoid arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 113 publications
(82 reference statements)
0
53
0
4
Order By: Relevance
“…The B‐cell depletion approach is an approved therapy for lymphoma patients and for some autoimmune diseases (Salles et al, ; Schioppo & Ingegnoli, ). A recent article has shown that B‐cell depletion in systemic sclerosis patients not only promotes remission but also temporarily reverses the disease‐restricted B‐cell repertoire due to new B‐cell generation (Bourcy, Dekker, Davis, & Nicolls, ).…”
Section: Discussionmentioning
confidence: 99%
“…The B‐cell depletion approach is an approved therapy for lymphoma patients and for some autoimmune diseases (Salles et al, ; Schioppo & Ingegnoli, ). A recent article has shown that B‐cell depletion in systemic sclerosis patients not only promotes remission but also temporarily reverses the disease‐restricted B‐cell repertoire due to new B‐cell generation (Bourcy, Dekker, Davis, & Nicolls, ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the suspected causal role of B lymphocytes in the pathogenesis of SS, rituximab (a monoclonal antibody that depletes B cells) has been used, with anecdotal responses. 305,306 Data on the effect of rituximab in pSS are mixed. Gottenberg et al prospectively followed up 78 patients with systemic involvement of pSS in the AutoImmune and Rituximab (AIR) registry who were treated with rituximab.…”
Section: Rituximabmentioning
confidence: 99%
“…RTX is combined with several chemotherapies for treating B cell lymphoma and is used alone to treat autoimmune diseases such as rheumatism. Clinical trials have already provided evidence on the safety of RTX [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%